Planning for the opioid crisis: how four cities approach zoning of healthcare related facilities - Smith, Emma-Quin K. (Kansas State University, 2019)
As the opioid epidemic continues to ravage the United States, there are a variety of structural and societal causes of the epidemic that must be explored in order to produce a sustainable solution to the problem. According to the Centers for Disease Control (CDC), "a multifaceted, collaborative public health and law enforcement approach is urgently needed" (Rudd, 2016). The intersection of community social dynamics, public health, and planning is a critical area to study and can uncover the role that planners have to play in ending the crisis. This study seeks to answer the question "How do zoning and land use regulations affect the accessibility of substance abuse treatment facilities?" The purpose of this study is to determine an effective land use regulation and policy regime for the city of Springfield, Missouri, USA to employ in order to improve access to substance abuse treatment facilities (SATF). This topic is important to understand because knowing where there are gaps in accessibility to treatment will inform where to develop new treatment centers to treat a larger swath of the population. Improving access to treatment facilities improves the health and wellbeing of communities and reduces the time and financial cost of seeking treatment (Pearce, Witten, & Bartie, 2006). This study relies on zoning analysis and qualitative methods, plus a site suitability analysis to assess how Springfield, Missouri can update their zoning codes to provide increased accessibility to SATF facilities. The framework for this study is based on the methods used by Nemeth and Ross (2014). The analytic strategy for this project can be divided into three basic components: a zoning analysis, a socioeconomic disadvantage (SED) index, and site suitability analysis. ArcMap was used to map city zoning and socioeconomically disadvantaged census tracts, and also for land area calculations that contribute to a site suitability analysis. The maps produced demonstrate the accessibility of treatment centers via the permissiveness of zoning for potential locations of treatment centers using land area calculations. This study also demonstrates the availability of treatment according to an overlay of the zoning permissions and location of various population demographics via a socioeconomic disadvantage index. The study utilized Springfield, Missouri as the main study site. Regulation suites included in the analyses were Seattle, Washington, USA; Denver, Colorado, USA; and San Francisco, California, USA. Research findings suggest that Denver, CO provides the most equitable model for siting SATFs in Springfield despite the fact that the model is the least permissive. There are four key takeaways from this study: 1.) Syntax matters. SATF are human health services and can be retail service uses; 2.) Normalizing seeking treatment can start with co-locating facilities in established retail developments; 3.) Quality of permitted zones should be considered over quantity of permitted use zones; 4.) Utilize additional zoning tools such as districts and conditional use zones. This limited sample indicates that cities must carefully consider zoning regulations in order to promote both high equity and high permissiveness in siting SATFs. This could be an area for further study in providing high quality treatment to all segments of the population.
Keywords: Opioid crisis; Urban planning; Public health; Land use regulations